PENGARUH POLA ASUH ORANG TUA BERDASARKAN STATUS SOSIAL EKONOMI TERHADAP PERILAKU BERKARAKTER SISWA DI SMP NEGERI 4 KERITANG KABUPATEN INDRAGIRI HILIR - Andi Zainudin; Hambali '; Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this research by declining student character behavior, such as smoking, fighting, truancy, coming late to school, speak dirty, which is closely related to the parents' parenting is based on the level of socio-economic status. formulation of the problem in this research is (1) How the influence of parenting parents of high socio-economic status based on the behavior of the character of students in SMP Negeri 4 Keritang Kabupaten Indragiri Hilir. (2) How the influence of parenting parents of middle socio-economic status based on the behavior of the character of students in SMP Negeri 4 Keritang Kabupaten Indragiri Hilir. (3) How the influence of parenting parents of low socio-economic status based on the behavior of the character of students in SMP Negeri 4 Keritang Kabupaten Indragiri Hilir. Sampling by using purposive sampling by taking 15 students each level of socio-economic status. Descriptive quantitative analysis techniques with multiple linear regression using SPSS version 16.Based on the results of the research, at the level of high socio-economic status, of the significance test is obtained Fcount 7,130 > Ftable 3,59 thus Ho is rejected and Ha accepted, meaning that there is significant influence parenting parents of high socio-economic status based on the behavior of the character of students in SMP Negeri 4 Keritang Kabupaten Indragiri Hilir. at the level of middle socio-economic status, of the significance test is obtained Fcount 3,773 > Ftable 3,59, thus Ho is rejected and Ha accepted, meaning that there is significant influence parenting parents of middle socio-economic status based on the behavior of the character of students in SMP Negeri 4 Keritang Kabupaten Indragiri Hilir. at the level of lower socio-economic status, of the significance test is obtained Fcount 6,267 > Ftable 3,59, thus Ho is rejected and Ha accepted, meaning that there is significant influence parenting parents of low socio-economic status based on the behavior of the character of students in SMP Negeri 4 Keritang Kabupaten Indragiri Hilir.Keywords: Parenting Parents, Socio-Economic Status, Behavior Character.2PENGARUH POLA ASUH ORANG TUA BERDASARKAN STATUS